2022
DOI: 10.1007/s11469-022-00782-5
|View full text |Cite
|
Sign up to set email alerts
|

Problematic Internet Use Among University Students in Jamaica

Abstract: The prevalence of problematic Internet use (PIU) and its associated negative outcomes among college students has been heavily researched in developed countries. However, despite the increased accessibility of the Internet and indicators which may suggest PIU in developing countries such as Jamaica, PIU in this context remains grossly understudied. This study surveyed 277 Jamaican university students and found evidence of PIU, with younger respondents (ages 18–23) at risk. The findings also indicate that the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Which indicates students with high depressive symptom scores had a high PIU score as compared to their counterparts, keeping other variables in the model controlled. This finding was supported by previous reports [ 5 , 13 , 17 , 23 , 25 , 27 , 57 – 62 ]. This might be due to the fact that students with depressive symptoms may use the internet and other social media to relieve their loneliness, emotional distress, and unhealthy lifestyle [ 9 , 63 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Which indicates students with high depressive symptom scores had a high PIU score as compared to their counterparts, keeping other variables in the model controlled. This finding was supported by previous reports [ 5 , 13 , 17 , 23 , 25 , 27 , 57 – 62 ]. This might be due to the fact that students with depressive symptoms may use the internet and other social media to relieve their loneliness, emotional distress, and unhealthy lifestyle [ 9 , 63 ].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, factors such as age [ 10 , 16 18 ], sex [ 5 , 9 , 19 21 ], poor sleep quality [ 22 ], less frequent exercise [ 23 ], year of study [ 18 ], marital status [ 10 ], residence [ 24 ], alcohol consumption [ 4 , 21 , 24 ], perceived social support [ 24 , 25 ], psychological distress [ 4 , 13 , 17 , 24 ], smoking [ 21 ], ADHD symptoms [ 26 ], depressive symptoms [ 5 , 9 , 13 , 17 , 23 , 25 , 27 ], chat chewing, and caffeinated drinks [ 4 , 5 ] were indicated as significant factors associated with PIU.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has indicated that the proportion of people with PIU is greater in low-income countries, and PIU has shown more prevalence among university students. However, the number of these studies is still small [15][16][17]. Even though recent studies have discussed this phenomenon, the number of these studies is still small, especially for the categories of university students, where we can see a significant rise in depression rates every year; therefore, this topic must be studied more with a concentration on university students to minimize the occurrence of this issue.…”
Section: Introductionmentioning
confidence: 99%
“…However, the number of these studies is still small. [14][15][16] Even though recent studies have discussed this phenomenon, the number of these studies is still small, especially for the categories of university students, where we can see a signi cant rise in depression rates every year; therefore, this topic must be studied more with a concentrate on university students In order to minimize the occurrence of this issue. This study aims to measure the correlation between depression and internet addiction, especially among Syrian college students on social media like Facebook.…”
mentioning
confidence: 99%